The Influence of Audit Committees on the Financial Viability of Real Estate Companies in Indonesia - Natasha Elisabeth Manuputty; Agus Munandar (Green Publisher, 2025)
Alignment with the company's commitment to implementing good governance so it can support the company's goal of improving performance. The intention of this study is to determine the role of the audit committee in the company's financial viability. The findings show that audit committee size has a positive but insignificant effect on company financial viability. Financial expertise possessed by audit committee has a negative and insignificant effect on financial viability, while audit committee independence also has a negative and insignificant effect on financial viability. Simultaneously, the three audit committee characteristic variables do not significantly influence company financial viability, as indicated by the F-statistic probability value of 0.317 (>0.05). The conclusion of this study show that audit committee characteristics do not take part in significant role in improving company financial viability. Therefore, companies are advised to not only heed to the formal structure of the audit committee but also to improve the effectiveness, frequency of meetings, and quality of audit committee oversight to ensure they can make a significant contribution to company viability.